SPSS statistics for dummies - McCormick, Keith (Consultant); Salcedo, Jesus (Consultant); Poh, Aaron (Consultant) (Hoboken, New Jersey : John Wiley & Sons, Inc., 2015)
If you work in a field that uses SPSS Statistics, you may have found it overwhelming. The authors of this guide get you up and running and how you how to get the most from your data.
pt. I. Getting started with SPSS -- pt. II. Getting data in and out of SPSS -- pt. III. Messing with data in SPSS -- pt. IV. Graphic data -- pt. V. Analyzing data -- pt. VI. Making SPSS your own : settings, templates, and looks -- pt. VII. Programming SPSS with command syntax -- pt. VIII. The part of tens.
Includes index.
Keywords: SPSS (Computer file); SPSS (Computer file); Social sciences -- Statistical methods -- Computer programs -- Handbooks, manuals, etc; Social sciences -- Statistical methods -- Computer programs; Handbooks and manuals